2019
DOI: 10.7717/peerj.6240
|View full text |Cite
|
Sign up to set email alerts
|

Use of a leaf chlorophyll content index to improve the prediction of above-ground biomass and productivity

Abstract: Improving the accuracy of predicting plant productivity is a key element in planning nutrient management strategies to ensure a balance between nutrient supply and demand under climate change. A calculation based on intercepted photosynthetically active radiation is an effective and relatively reliable way to determine the climate impact on a crop above-ground biomass (AGB). This research shows that using variations in a chlorophyll content index (CCI) in a mathematical function could effectively obtain good s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 48 publications
4
61
0
3
Order By: Relevance
“…Based on the phenological growth/BBCH stages, the mean CCI values in the current study for the tillering stage, booting stage, filling stage, and maturity stage were 6.0, 16.9, 23.0, and 14.2, respectively. In accordance, Liu et al [29] concluded that at the same growth stages the median CCI values were 21.1, 43.1, 41.1, and 18.9, respectively. In both studies, the CCI values followed the same trend: a growth path until the filling stage and then a decrease until the maturity stage.…”
Section: Significance Of F Ratiosupporting
confidence: 65%
See 2 more Smart Citations
“…Based on the phenological growth/BBCH stages, the mean CCI values in the current study for the tillering stage, booting stage, filling stage, and maturity stage were 6.0, 16.9, 23.0, and 14.2, respectively. In accordance, Liu et al [29] concluded that at the same growth stages the median CCI values were 21.1, 43.1, 41.1, and 18.9, respectively. In both studies, the CCI values followed the same trend: a growth path until the filling stage and then a decrease until the maturity stage.…”
Section: Significance Of F Ratiosupporting
confidence: 65%
“…According to Peng et al [30], CCI is a good indicator for the evaluation of compost effects on rice cultivation, whereas chlorophyll meters can be used for monitoring leaf nitrogen status in rice, since rice plants with higher nitrogen content have higher chlorophyll content and consequently higher CCI values [31]. Chlorophyll provides an indication of the nutritional status as a result of nitrogen absorption and utilization, which serves as a reliable means to estimate the function of the nitrogen fertilizer [29] and this is confirmed from our results.…”
Section: Significance Of F Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The efficient photosynthesis is extremely important, because it determines the crop yield and the effectiveness of capturing the light and transforming it into the biomass [ 33 ]. The chlorophyll in leaves is a major indicator of the leaf greenness, and is frequently determined to verify the nutrient deficiencies (e.g., nitrogen and the changes in its content) [ 34 ]. There is a substantial link between the amount of chlorophyll and leaf nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Klorofil merupakan pigmen pada tanaman yang berperan penting dalam menentukan laju fotosintesis dan pertumbuhan tanaman (Li et al, 2018) dan berasosiasi kuat dengan kandungan mineral Fe (Rodrigues et al, 2015). Laju fotosintesis berkorelasi sangat kuat dengan karakter daya hasil (Karademir, Karademir, Ekinci, & Gençer, 2008;Liu et al, 2019), khususnya pada tanaman kopi (R=0,94*) (Reis et al, 2009).…”
Section: Karakter Morfofisiologi Daununclassified